1969
DOI: 10.1071/ar9690925
|View full text |Cite
|
Sign up to set email alerts
|

The digestion of pasture plants by sheep. IV*. The digestion of Phalaris tuberosa at different stages of maturity

Abstract: A study was made of the composition, intake, and digestion of dried Phalaris tuberosa forage that had been harvested at three stages of maturity. Advancing maturity was associated with: (i) decreased food intake; (ii) increased expenditure of time and energy in chewing activities; (iii) decline in the rate of flow of digesta from the abomasum though not from the rumen; (iv) decline in digestibility in the whole tract of organic matter, nitrogen, and the structural carbohydrates; (v) decline in the digestion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
13
2

Year Published

1976
1976
2001
2001

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 0 publications
7
13
2
Order By: Relevance
“…The results of Hogan et al (1969) and Playne & Kennedy (1976) are in concordance with these findings. Proportions of propionic acid decreased (P < 0.05) as herbage matured during summer and autumn.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The results of Hogan et al (1969) and Playne & Kennedy (1976) are in concordance with these findings. Proportions of propionic acid decreased (P < 0.05) as herbage matured during summer and autumn.…”
Section: Resultssupporting
confidence: 81%
“…Rumen NH 3 -N levels decreased as pasture matured during all seasons (Table 4). Hogan et al (1969) also observed a decrease in rumen NH 3 -N levels with advancing forage maturity. Rumen NH 3 -N concentrations were the highest in summer, followed by autumn and winter which corresponds with the results of Meissner et al (1993).…”
Section: Resultsmentioning
confidence: 85%
“…However, there are several other changes associated with advancing maturity that contribute to the lowering of the nutritive value of grass forage. Thus Hogan et al (1969) showed that for P. tuberosa there was a decreased intake; an increased expenditure of time and energy in chewing activities; a decline in rate of flow of digesta from the abomasum, though not from the rumen; a decline in digestibility, in the whole tract, of organic matter N and structural carbohydrates; a decline in digestion of fibre in the rumen relative to that occurring in the whole tract; and a decline in quantities of volatile fatty acids and amino acids made available to the animal.…”
Section: Maturity Digestibility and Cell Wall Constituentsmentioning
confidence: 99%
“…Relationship between organic matter digested in the stomach and organic matter apparent digestibility in sheep fed a wide range of diets. Data used include: (A)Ulyatt & MaeRae, 1974; (B) present paper; (C)Beever et al 1972; Egan et al 1975;(E) Egan, 1974; Nicholson & Sutton, 1969; Thomson et al 1972; Hogan & Weston, 1967a; (I) (J)Hogan, Weston & Lindsay, 1969;(K) …”
mentioning
confidence: 99%